Gas Sensing Properties of Nanojunction of Networked ZnO Nanowires under the Correlation Between Operating Temperature and UV Radiation - Nguyen, Manh Hung; Chu, Manh Hung; Nguyen, Van Hieu (Communications in Physics, 2021)
The networked ZnO nanowires (NWs) are synthesized by thermal evaporation at 900oC, using a mixture of ZnO and graphite. The morphology, crystalline structure, and chemical composition of the NWs are evaluated by field-emission scanning electron microscopy, X-ray diffraction, and energy-dispersive spectrum. The NO\(_2\) gas-sensing properties of a networked ZnO NWs-based sensor are considered in a correlation between the operating temperature and UV radiation with various operating temperatures as well as UV intensities. The results reveal that the sensing properties of the UV-illuminated sensor measured at room temperature are comparable to those of the heated sensor. The results also indicate that the UV intensity affects strongly both the response and the sensing kinetic of the sensor at all operating temperatures. Furthermore, based on a systematic investigation of the sensing performance of the sensor under both UV illumination and thermal activation, a model to explain the role of UV illumination is also proposed.